Ex vivo Akt inhibition promotes the generation of potent CD19CAR T cells for adoptive immunotherapy - Stephen J. Forman; Ryan Urak; Miriam Walter; Laura Lim; ChingLam W. Wong; Lihua E. Budde; Sandra Thomas; Xiuli Wang (Journal for ImmunoTherapy of Cancer)
Background Insufficient persistence and effector function of chimeric antigen receptor (CAR)-redirected T cells have been challenging issues for adoptive T cell therapy. Generating potent CAR T cells is of increasing importance in the field. Studies have demonstrated the importance of the Akt pathway in the regulation of T cell differentiation and memory formation. We now investigate whether inhibition of Akt signaling during ex vivo expansion of CAR T cells can promote the generation of CAR T cells with enhanced antitumor activity following adoptive therapy in a murine leukemia xenograft model.Methods Various T cell subsets including CD8+ T cells, bulk T cells, central memory T cells and naïve/memory T cells were isolated from PBMC of healthy donors, activated with CD3/CD28 beads, and transduced with a lentiviral vector encoding a second-generation CD19CAR containing a CD28 co-stimulatory domain. The transduced CD19CAR T cells were expanded in the presence of IL-2 (50U/mL) and Akt inhibitor (Akti) (1 μM) that were supplemented every other day. Proliferative/expansion potential, phenotypical characteristics and functionality of the propagated CD19CAR T cells were analyzed in vitro and in vivo after 17-21 day ex vivo expansion. Anti-tumor activity was evaluated after adoptive transfer of the CD19CAR T cells into CD19+ tumor-bearing immunodeficient mice. Tumor signals were monitored with biophotonic imaging, and survival rates were analyzed by the end of the experiments.Results We found that Akt inhibition did not compromise CD19CAR T cell proliferation and expansion in vitro, independent of the T cell subsets, as comparable CD19CAR T cell expansion was observed after culturing in the presence or absence of Akt inhibitor. Functionally, Akt inhibition did not dampen cell-mediated effector function, while Th1 cytokine production increased. With respect to phenotype, Akti-treated CD19CAR T cells expressed higher levels of CD62L and CD28 as compared to untreated CD19CAR T cells. Once adoptively transferred into CD19+ tumor-bearing mice, Akti treated CD19CAR T cells exhibited more antitumor activity than did untreated CD19CAR T cells.Conclusions Inhibition of Akt signaling during ex vivo priming and expansion gives rise to CD19CAR T cell populations that display comparatively higher antitumor activity.